HupZ, a Unique Heme-Binding Protein, Enhances Group A Streptococcus Fitness During Mucosal Colonization - Lyles, Kristin V.; Thomas, Lamar S.; Ouellette, Corbett; Cook, Laura C. C.; Eichenbaum, Zehava (Frontiers in Cellular and Infection Microbiology, 2022)
Group A Streptococcus (GAS) is a major pathogen that causes simple and invasive infections. It requires iron for metabolic processes and pathogenesis and heme is its preferred host source of iron. We previously described the iron-regulated hupZ in GAS and showed that a recombinant HupZ-His6 protein binds and degrades heme in vitro, though the His6 tag was implicated in heme iron coordination by HupZ-His6. We tested two HupZ recombinants proteins, demonstrating that HupZ binds heme without a His6 tag and without coordinating the heme iron. It readily accepted exogenous imidazole as its axial heme ligand, prompting degradation in vitro. HupZ bound a fragment of heme c (whose iron is coordinated by the cytochrome histidine residue) but exhibited limited degradation. In vivo, heterologous HupZ expression in Lactococcus lactis increased heme-iron use. A GAS hupZ mutant showed reduced growth when using hemoglobin as an iron source, increased sensitivity to heme toxicity, and decreased fitness in a murine model for vaginal colonization. Together, the data demonstrate HupZ contributions to heme metabolism and host survival, likely as a heme chaperon. HupZ is structurally similar to the recently described heme c degrading enzyme, Pden_1323, suggesting an emerging group of proteins that play new roles in bacterial heme metabolism.